National Development Council 28th Meeting May 30 & 31 1972 Summary Record - Planning Commission (Planning Commission, Government of India, 1972)
The 28th meeting of the National Development Council, held in May 1972, marked a significant turning point in India’s development planning as it laid the groundwork for the Fifth Five-Year Plan (1974–1979). The meeting brought together national and state leadership to reassess development priorities in light of persistent poverty, unemployment, and regional imbalances. Moving beyond a narrow focus on economic growth, the Council emphasized a direct attack on poverty through employment generation, equitable income distribution, and the provision of basic minimum needs such as education, healthcare, housing, drinking water, and rural electrification. The discussions highlighted the urgency of mobilizing substantial financial resources, implementing effective land reforms, and strengthening infrastructure to support inclusive growth. Special attention was given to addressing regional disparities and empowering states with greater flexibility in planning and resource allocation. The Approach Paper for the Fifth Five-Year Plan further underscored the need to curb excessive urban migration by improving rural livelihoods, promoting labor-intensive industries, enhancing vocational education, and upgrading urban infrastructure, particularly slum development. Environmental concerns, administrative efficiency, price stability, and sustainable employment programs were also integral to the strategy. Overall, the deliberations reflected a coordinated national effort to reshape India’s development strategy toward social justice, self-reliance, and balanced regional growth, aiming to significantly improve the living standards of the country’s poorest populations.
Government of India, Planning Commission
Keywords: National Development Council; Fifth Five-Year Plan; Poverty Alleviation; Employment Generation; Basic Minimum Needs; Resource Mobilization; Land Reforms; Regional Disparities; Rural Development; Urban Migration; Infrastructure Development; Administrative Efficiency